2020
DOI: 10.1111/cas.14298
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the gut microbiome in multistep colorectal carcinogenesis

Abstract: Colorectal cancer (CRC) is highly prevalent worldwide. In 2018, there were over 1.8 million new cases. Most sporadic CRC develop from polypoid adenomas and are preceded by intramucosal carcinoma (stage 0), which can progress into more malignant forms. This developmental process is known as the adenoma‐carcinoma sequence. Early detection and endoscopic removal are crucial for CRC management. Accumulating evidence suggests that the gut microbiota is associated with CRC development in humans. Comprehensive charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 46 publications
3
51
1
1
Order By: Relevance
“…The present study identified a significant elevation of P. micra in CRC but not in CRA cases. Consistent with these findings, it has been shown that P. micra is predominantly enriched in stages I/II and III/IV, and its abundance is decreased after tumor resection, indicating that P. micra is not the cause of carcinogenesis but is adapted to the CRC microenvironment (50,51). Therefore, P. micra may be a passenger in the driver-passenger model.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The present study identified a significant elevation of P. micra in CRC but not in CRA cases. Consistent with these findings, it has been shown that P. micra is predominantly enriched in stages I/II and III/IV, and its abundance is decreased after tumor resection, indicating that P. micra is not the cause of carcinogenesis but is adapted to the CRC microenvironment (50,51). Therefore, P. micra may be a passenger in the driver-passenger model.…”
Section: Discussionsupporting
confidence: 55%
“…A previous study demonstrated that APC Min/+ mice gavaged with P. micra exhibited a significantly higher tumor burden and tumor load, and cell proliferation was significantly higher in the colon tissues of P. micra gavaged germ-free mice compared with control mice (56). Furthermore, the tumor promoting effect of P. micra has been reported to be associated with altered immune responses and increased inflammation in the gut (50,56). These findings indicate that P. micra is primarily adapted to the CRC microenvironment and could contribute to a pro-tumoral inflammatory environment in patients susceptible to developing CRC.…”
Section: Discussionmentioning
confidence: 99%
“…CRC-related microbiota could be classified to three distinct patterns (Mizutani et al, 2020). First, the abundances of gut microbes such as pro-inflammatory bacteria were elevated from stage 0 to more advanced stages, such as Fusobacterium nucleatum, Peptostreptococcus anaerobius, Peptostreptococcus stomatis, and Parvimonas micra., P. anaerobius, P. stomatis and P. micra were predominantly enriched in stage I/II and stage III/IV, and their abundances decreased after tumor resection, which implies that these species might not cause carcinogenesis but were adapted to the cancerous environment (Yachida et al, 2019).…”
Section: Changes In the Gut Microbiota Associated With Crcmentioning
confidence: 99%
“…The abundance of different microbiota also varies highly among healthy individuals depending on environmental conditions, genetics, the host’s immune system, diet as well as infections or use of antibiotics [ 9 , 10 ]. In colorectal cancer (CRC), there is an increasing evidence suggesting that the gut microbiota are associated with CRC development [ 11 , 12 ]. Gut microbiota show significant impact on processes involved in cellular DNA damage, DNA methylation, chromatin structure modulation and non-coding RNA expression [ 1 ].…”
Section: Introductionmentioning
confidence: 99%